Анекдот як складова сміхової культури (Літератури світу: поетика, ментальність і духовність, 2017)
The article defines the features of the correlation of the joke and the culture of laughter (complete and incomplete, the compound of destructive and creative potential, and so on). The interdependence of the joke and the culture is highlighted (culture provides the material for inverting, joke prevents the «ossification» of culture). The implementation of the anti-behavior in the joke at level of the characters and at the level of the interlocutors is detected. The types of laughter, which are implemented in the joke and in the reaction to it, are defined. The article notes the dependence the joke from the historical period of transition at the level of such features of the genre as a cynicism, absurd etc.
Keywords: анекдот; сміхова культура; сміховий антисвіт; антиповедінка; гумор; сатира; культура; перехідний історичний період